Peripheral Tumor Location Predicts a Favorable Prognosis in Patients with Resected Small Cell Lung Cancer - Yina Gao; Yangyang Dong; Yingxu Zhou; Gongyan Chen; Xuan Hong; Qingyuan Zhang (International Journal of Clinical Practice)
Background. Small cell lung cancer (SCLC) is an aggressive malignancy. Surgical resection is currently only recommended for clinical stage I patients who have been carefully staged. The clinical outcomes of patients with resected SCLCs vary because the disease is highly heterogeneous, suggesting that selected patients could be considered for surgical resection depending on their clinical and/or molecular characteristics. Methods. We collected data on a retrospective cohort of 119 limited-stage SCLC patients who underwent lobectomy with mediastinal lymph node dissection from March 2013 to March 2020 at Harbin Medical University Cancer Hospital. Correlations were derived using Fisher’s exact test. Models of 2-year and 3-year survival were evaluated by deriving the area under receiver operating characteristic curves. Kaplan–Meier and Cox regression analyses were used to evaluate significant differences between the survival curves and hazard ratios. Results. The median disease-free survival (DFS) was 35.9 months (range 0.9–105.3 months), and the median overall survival (OS) was 45.2 months (range 4.8–105.3 months). Univariate analysis showed that TNM stage was significantly correlated with DFS and OS. The 2-year disease-free rates of patients with stage I, II, and III disease were 76.4%, 50.5%, and 36.1%, respectively, and the 3-year OS rates were 75.9%, 57.7%, and 34.4%, respectively. In pN + patients, multiple (or multiple-station) lymph node involvement significantly increased recurrence and reduced survival compared with patients with single or single-station metastases. Patients with peripheral SCLCs evidenced significantly better DFS and OS than did patients with central tumors. Multivariate analysis showed that TNM stage and tumor location were independently prognostic in Chinese patients with resected limited-stage SCLC. A combination of TNM stage and tumor location was helpful for prognosis. Conclusions. TNM stage and tumor location were independently prognostic in Chinese patients with resected SCLCs. Patient stratification by tumor location should inform the therapeutic strategy. The role of surgical resection for limited-stage SCLC patients must be reevaluated, as this may be appropriate for some patients.